The Role of Professional Quality of Life in Physical and Psychological Health of Textile Employees - Rasheed, Ayesha (UIN Sunan Kalijaga, 2022)
The quality of life in employees is an issue that must be examined as it is a crucial point for organization or industry growth. This study aims to investigate the correlation between professional quality of life with physical and psychological health in textile sector employees. Study was conducted on (N=150, male and female employees) employees from 19 textile companies in Lahore city, Pakistan. A correlational research design was used, and sample was selected by using stratified sampling technique. A series of questionnaire (Professional Quality of life and (SF-12) Short Form-12 Health survey) was administered to employees after taking consent from the them. The results indicate that quality of life has relationship with physical and psychological health. Specifically, compassion satisfaction aspect has positive significant relationship with physical and mental health component while inverse relationship with burnout and compassion fatigue. When compassion satisfaction increases, the physical and psychological health of the workers improved and vice versa. Similarly, when burnout and compassion fatigue increase, it affected the physical and psychological health of the workers. It is recommended to the organization to make plans and policies to boost up employees mental and physical health. Kualitas hidup karyawan merupakan masalah yang harus diperhatikan terutama dalam dunia kerja. Penelitian ini bertujuan untuk mengetahui hubungan antara kualitas hidup professional dengan kesehatan fisik dan psikologis pada karyawan sektor tekstil. Studi dilakukan pada (N=150, karyawan pria dan wanita) karyawan dari 19 perusahaan tekstil di kota Lahore, Pakistan. Rancangan penelitian yang digunakan adalah korelasional, dan sampel dipilih dengan menggunakan teknik stratified sampling. Serangkaian kuesioner (Professional Quality of life dan (SF-12) Short Form-12 Health survey) diberikan kepada karyawan setelah mendapat persetujuan dari mereka. Hasil penelitian menunjukkan bahwa kualitas hidup memiliki hubungan dengan kesehatan fisik dan psikologis. Secara khusus, aspek compassion satisfaction memiliki hubungan positif yang signifikan dengan komponen kesehatan fisik dan mental, sedangkan hubungan terbalik dengan burnout dan compassion fatigue. Ketika compassion satisfacion meningkat, kesehatan fisik dan psikologis pekerja meningkat dan sebaliknya. Demikian pula ketika burnout dan compasison fatigue meningkat, hal itu mempengaruhi kesehatan fisik dan psikologis para pekerja. Disarankan kepada organisasi untuk membuat rencana dan kebijakan untuk meningkatkan kesehatan mental dan fisik karyawan.